Climate Change Adaptation Strategies of Smallholder Agroforestry Farmers in the Philippines - Landicho, Leila D. (Journal of Environmental Science and Management, 2016)
This article argues that smallholder agroforestry farmers in the selected provinces in the Philippines have already been experiencing climate change in their respective areas as indicated by the change in the rainfall and temperature patterns. Using direct interviews and focus group discussions, the respondent-farmers highlighted that increased incidence of pests and diseases, stunted growth of crops, low crop productivity, delayed planting, delayed fruiting of some crops particularly perennial species, poor quality of produce, increased cost in farm operations, low income and decreased yield of some crops, are among the general impacts of climate change in their agricultural production systems. On the positive aspect, some crops had increased yield as an impact of climate change. The farmers employ their local knowledge and skills in adapting to the impacts of climate change. Among these include changing cropping patterns, integrating more crops in the farm, engaging in other off-farm and non-farm activities as additional source of income, changing the cultivated crops, mulching, and using organic fertilizers, among others. This article also highlights the benefits that the respondent-farmers derive from agroforestry, a land use management system that is currently being practiced in the study sites.